A bridge between values: municipal heritage policies, plurality of meanings, and alternatives to the Anthropocene in the South of Minas Gerais (PerCursos, 2021)
The article discusses the listing process of the Ponte das Amoras, which connects the municipalities of Alfenas and Campos Gerais over the flooded area of the Sapucaí River by the Furnas Hydroelectric Plant. Therefore, the argument is based on some theoretical issues related to heritage policies in times of climatic emergency and the plurality of meanings and values that permeate these policies. We also discuss the conflicts that emerged around the implementation of the Furnas Dam in the region and the specific characteristics of heritage policies in the state of Minas Gerais. Finally, we assess the implementation of these policies considering the plurality of meanings and values linked to the Ponte das Amoras through interviews conducted with the managers involved in the registration process and through a survey conducted with residents of Alfenas and region, proposing, from that, alternatives to these policies that consider the need to produce fairer futures and that can face the current biogeophysical and climatic imbalance that characterizes the time of the Anthropocene.
Keywords: heritage; cultural significance; climate changes